2020
DOI: 10.1038/s41408-020-0282-9
|View full text |Cite
|
Sign up to set email alerts
|

The RUNX1-ETO target gene RASSF2 suppresses t(8;21) AML development and regulates Rac GTPase signaling

Abstract: Large-scale chromosomal translocations are frequent oncogenic drivers in acute myeloid leukemia (AML). These translocations often occur in critical transcriptional/epigenetic regulators and contribute to malignant cell growth through alteration of normal gene expression. Despite this knowledge, the specific gene expression alterations that contribute to the development of leukemia remain incompletely understood. Here, through characterization of transcriptional regulation by the RUNX1-ETO fusion protein, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Having observed that let-7b-5p overexpression can reduce AML1-ETO protein expression, we next wondered whether the degree of AML1-ETO downregulation has potential therapeutic relevance. Therefore, we first measured the expression of known transcriptionally repressed AML1-ETO target genes, CEBPA [17] and RASSF2 [59], upon transfection of Kasumi-1 and SKNO-1 cells with the let-7b-5p miRNA mimic. In both cell lines, treatment with the miRNA mimic resulted in a significant increase of both transcripts in comparison to cells treated with a non-targeting control mimic (Fig.…”
Section: Expression Of Let-7b Inhibits Cell Growth In T(8;21) Aml Cell Linesmentioning
confidence: 99%
“…Having observed that let-7b-5p overexpression can reduce AML1-ETO protein expression, we next wondered whether the degree of AML1-ETO downregulation has potential therapeutic relevance. Therefore, we first measured the expression of known transcriptionally repressed AML1-ETO target genes, CEBPA [17] and RASSF2 [59], upon transfection of Kasumi-1 and SKNO-1 cells with the let-7b-5p miRNA mimic. In both cell lines, treatment with the miRNA mimic resulted in a significant increase of both transcripts in comparison to cells treated with a non-targeting control mimic (Fig.…”
Section: Expression Of Let-7b Inhibits Cell Growth In T(8;21) Aml Cell Linesmentioning
confidence: 99%
“… 17 We then extracted subsets of genes that significantly contributed to the gene enrichment (called “core enrichment genes”, defined by GSEA) for the above two gene sets (Figure S1B ). Indeed, 27 and 16 core enrichment genes were commonly upregulated in SKNO‐1 and Kasumi‐1 for the two gene sets, respectively, which included OGG1 that is involved in base excision repair in AML1‐ETO‐mediated mutagenesis, 35 tumor suppressors RASSF2 36 and TGFBI , 37 and also LAT2 that blocks differentiation in t(8;21)‐positive cells 38 as repressive targets of AML1‐ETO. We further found that KDM4B silencing in SKNO‐1 but not Kasumi‐1 had inhibitory effects on the expression of a broader range of AE‐inducible genes (Figure 2I ), which was compatible with an intensive growth‐suppressive effect following the gene silencing (Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity of expression pro les has been studied for AML patients harboring different mutations or chromosomal abnormality [11][12][13][14], but the co-expressed gene modules have not been rarely linked to the genetic markers using WGCNA. Ravasz et al demonstrated hierarchical network modularity for metabolic network, based on which they proposed the utility of Topological Overlap Matrix to measure how strongly the nodes are connected [15].…”
Section: Discussionmentioning
confidence: 99%